Global Warming as a Crime against Nature: Identifying the Principal Offenders - Combo, Aneha Kaur (International Journal of Criminology and Sociology, 2025)
This article employs a literature-based methodology, utilising green criminology literature and case examples to examine global warming through the framework of green criminology to assess whether contributions to global warming can be considered a ‘crime against nature’ due to their extensive environmental harm. Such environmental degradation aligns with the concept of ‘ecocide’, which criminalises acts that contribute to extensive damage or loss to the Earth’s ecosystems. The analysis identifies states and corporations as principal perpetrators, highlighting how fossil fuel industries contribute to global warming through environmentally detrimental practices and climate misinformation campaigns. Simultaneously, the actions of the state, such as obstructing climate change policies and appointing industry-affiliated personnel to key regulatory positions, exacerbate the climate crisis. While individual consumer behaviours are also contributory, these actions are largely constrained by the systems that are heavily influenced by state-corporate interests. Reframing global warming as a crime against nature highlights the urgent need for legal accountability and systemic reform to address the climate crisis. Recognition of ‘ecocide’ by the International Criminal Court would enable corporate and state actors to be held accountable for their harmful contribution to global warming.